2022
DOI: 10.1249/tjx.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Recommendation Standards to Evaluate a Cancer-Specific Community-Based Exercise Program

Abstract: Physical activity (PA) is an important health behavior associated with improved physical functioning (1), well-being (1), and length of survival (2) for individuals living with and beyond cancer (i.e., survivors). However, after completion of active treatment, it has been reported that a large proportion of survivors do not meet established PA guidelines of ≥150 min of moderate-intensity PA per week (3,4). For many, treatment-related functional limitations persist months to years after treatment completion (5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The current study also demonstrated statistically significant improvements in muscular endurance, as measured by the number of bicep-curl repetitions (with a 5-lb resistance band) and sit-to-stand repetitions completed in 30 s. This finding is consistent with a previous telehealth intervention for breast cancer survivors, which elicited large improvements in handgrip and sit-to-stand (16). The effect size observed for sit-to-stand repe-titions (d = 0.55) was smaller than observed following the faceto-face Fit Cancer program (d = 0.62) (21), similar to a study in breast and prostate cancer survivors that found smaller improvements in chair stand time when their in-person exercise intervention was adapted for videoconference delivery (20).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current study also demonstrated statistically significant improvements in muscular endurance, as measured by the number of bicep-curl repetitions (with a 5-lb resistance band) and sit-to-stand repetitions completed in 30 s. This finding is consistent with a previous telehealth intervention for breast cancer survivors, which elicited large improvements in handgrip and sit-to-stand (16). The effect size observed for sit-to-stand repe-titions (d = 0.55) was smaller than observed following the faceto-face Fit Cancer program (d = 0.62) (21), similar to a study in breast and prostate cancer survivors that found smaller improvements in chair stand time when their in-person exercise intervention was adapted for videoconference delivery (20).…”
Section: Discussionsupporting
confidence: 87%
“…When compared with group-based videoconference PA interventions in other populations, increases in PA in the current study were larger: an average increase of 114.3 min•wk −1 of total MVPA in the current study versus 34.9 min of MVPA per week in a study of mothers (38), and 23.9 moderate PA minutes per week in a study of adults with Alzheimer's disease (39). It is difficult to ascertain the reason(s) for the larger increases in MVPA in our study compared with these two other studies; however, potential explanations could be the method of assessing PA (e.g., steps using an activity tracker vs self-reported aerobic and resistance exercise in the current study), population characteristics, Regarding QOL, two subscales (emotional and functional well-being) as well as total QOL showed a statistically significant increase, with small to medium effect sizes, which was similar to the face-to-face Fit Cancer program (21). One previous study also found that an 8-wk telehealth exercise intervention improved QOL with larger effect sizes than the current study; however, those participants were all postadjuvant treatment, and exercise sessions were held three times per week (16).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation